Efficacy and safety of vedolizumab in elderly and younger patients with moderate-to-severe ulcerative colitis: a retrospective real-world study in China - Hao Zhang; Xue-Li Ding; Yong-Hong Xu; Jun Wu; Yue-Yuan Wang; Shu-Xian Liu; Jing Yan; Hua Liu; Zi-Bin Tian; Ai-Ling Liu (BMC Gastroenterology)
Abstract Background Limited data exist regarding the efficacy and safety of vedolizumab (VDZ) in China’s elderly adult population with ulcerative colitis (UC) in China. In this investigation, a comparative analysis of its efficacy and safety was performed between elderly and younger adult UC cohorts. Methods Patients with moderate-to-severe UC and at least three VDZ infusions at our clinic between March 2021 and November 2024 were retrospectively recruited. The elderly adult patients (≥ 60 years at first VDZ dose) were matched clinically 1:2 to younger patients (18–59 years). Results This study included 30 elderly and 60 younger adult patients. There were no significant differences between the two groups regarding sex, body mass index, percentage of smokers, disease duration, disease extent, disease activity, Mayo endoscopic scores, extra-intestinal manifestations, perianal disease, history of bowel-related surgery, or previous and concomitant therapies. At week 6, the clinical remission and steroid-free clinical remission (SFCR) rates were significantly lower (10.00% vs. 33.33%, P = 0.017; 3.33% vs. 26.67%, P = 0.005) in the elderly group than in the younger group, but there was no significant difference in the clinical response rates (P = 1.000). There was no significant difference in the clinical response, remission, and SFCR rates between the two groups at weeks 14, 22, 38, 46, and 54 (P > 0.05). The frequency of adverse events associated with VDZ was comparable between the two groups (33.33% vs. 38.33%, P = 0.643). Conclusions The efficacy and safety of VDZ in elderly and younger adult patients with UC are similar. Thus, VDZ can be considered both safe and efficacious for treating elderly adult patients with UC.